Modification of Baseball Beater for Elementary School Physical Education Learning (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The loss of interest and the decrease of students 'motivation towards the ball game is one of the students' difficulties in doing the punch because the batter has a very small cross-section, so the student's punch is rarely about the ball. Research using R & D development method. Procedures of development research conducted are: (1) potential and problem, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) Product Testing, (7) trial usage. The subjects of this research are the students of 5th grade of Elementary School. Instruments and techniques of data collection using questionnaires, field notes, and documentation. The conclusion of this research is (1)